Electroacupuncture and Tongbian decoction ameliorate CUMS-induced depression and constipation in mice via TPH2/5-HT pathway of the gut-brain axis - Yi Chen; Peihua Shen; Qi Li; Shun Seng Ong; Yunzhi Qian; Hai Lu; Ming Li; Tianshu Xu (Brain Research Bulletin)
Depression is commonly associated with gastrointestinal (GI) disorders, such as constipation, which can potentially intensify depressive symptoms. The interplay between these conditions is believed to be facilitated by the gut-brain axis, which suggests a complex bidirectional interaction. Current treatments, such as antidepressants and prokinetics, are often associated with side effects and high recurrence rates, highlighting the need for effective treatments targeting both depression and constipation. This study was designed to assess the therapeutic efficacy of electroacupuncture (EA) in conjunction with Tongbian decoction (TB) for the management of both depression and constipation, while also investigating the underlying mechanisms through the lens of the gut-brain axis. Chronic unpredictable mild stress (CUMS) was employed to induce a comorbidity model of depression and constipation in mice, followed by the administration of EA, EA + TB, and fluoxetine (FLX). The findings of the study demonstrated that the antidepressant effects of electroacupuncture (EA) in combination with Tongbian decoction (TB) were more pronounced than those of EA alone. The EA + TB treatment significantly ameliorated depression and anxiety-like behaviors, restored cognitive function, and enhanced gastrointestinal motility in chronic unpredictable mild stress (CUMS) mice. Furthermore, EA + TB reduced intestinal inflammation, restored neuronal morphology, increased the expression of tryptophan hydroxylase 2 (TPH2) in both the prefrontal cortex (PFC) and colon, elevated the serum levels of 5-hydroxytryptophan (5-HTP)—a molecule that acts as a gut-brain connector—and promoted the synthesis and production of serotonin (5-HT) in both the gastrointestinal tract and the brain. Contrastingly, FLX showed limited efficacy in improving constipation. In conclusion, EA + TB regulates the TPH2/5-HT pathway via the gut-brain axis, demonstrating synergistic regulation of the nervous and gastrointestinal systems, with favorable antidepressant and prokinetic effects.